Favorable outcome in PLA2R positive HBV-associated membranous nephropathy - Ruiying Chen; Jia Wang; Qionghong Xie; Jianming Zheng; Shaojun Liu; Jun Xue; Chuanming Hao (BMC Nephrology, 2022)
Abstract Introduction Over half of the patients with hepatitis B virus associated membranous nephropathy (HBV-MN) were found to be phospholipase A2 receptor (PLA2R) positive. Whether MN is really secondary to hepatitis B or just coincidence of hepatitis and PLA2R positive idiopathic MN (IMN) remains controversial. Methods We retrospectively studied seven PLA2R positive HBV-MN patients with complete data in Huashan Hospital from 2009 to 2016 and compared them with PLA2R positive idiopathic MN patients. Results Proteinuria and renal function of these 7 HBV-MN patients were similar to that of IMN patients. However, 5 of them were female and half showed hypocomplementemia, while in IMN group only 32.4% were female and 20% had hypocomplementemia, and the level of hematuria was 94.5/μL in HBV-MN patients and 64.9 /μL in IMN patients, though there was no statistically significant difference. Renal biopsies revealed significantly increased mesangial eletron-deposits in HBV-MN patients. All 7 patients received antiviral therapy, and one patient received immunosuppresants due to severe nephrotic syndrome with acute myocardial infarction and elevated serum creatinine. Compared with IMN group, the prevalence of remission without immunosuppressive therapy of HBV-MN patients was higher (85.7% vs. 43.7%), while the percentage of patients receiving immunosuppresants was lower (14.3% vs. 47.9%) (P=0.048). Conclusion Compared with IMN patients, PLA2R positive HBV-MN patients had a more favorable prognosis after antiviral therapy, indicating a secondary form of MN. For these patients, antiviral treatment is recommended and long observation time should be provided before use of immunosuppressive treatment.